The Stability Diagram of a Single-Electron Transistor - Phoophathong, Titipong; Ritjareonwattu, Supachai (Food Agricultural Sciences and Technology, 2021)
A single-electron transistor (SET) is a promising technology, superseding a traditional transistor. This device needs to be accurately controlled by external voltage sources because this sophisticated structure is operated in the submicron scale. Quantum phenomena are employed to control a single-electron flow through the SET framework and to keep the electron in this framework. The number of excess electrons is important since it indicates the state of the device. External potentials can disturb the state constant. To forecast and specify the state, a mathematical model of the state transition was built. The model was then plotted as a stability diagram. The electrostatic energy was considered and analytically solved for the model. In this way, the complicated mathematics involved in this quantum phenomena could be simplified. The result strongly correlates with stability diagrams that were previously reported, however, the approach was different.